FIFA (Fédération Internationale de Football Association) the men, the myths and the money - Tomlinson, Alan (Routledge, Taylor & Francis Group, 2014)
"In this book, the history and underlying political dynamics characterizing the growth of FIFA and its relationships with global-regional federations and international associations are detailed in a helpful and concise introduction"--